2021
DOI: 10.3390/en14040797
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Flow Tidal Turbines with Highly Flexible Blades—Experimental Flow Field Investigations at Strong Fluid–Structure Interactions

Abstract: Oscillating hydrofoils were installed in a water tunnel as a surrogate model for a hydrokinetic cross-flow tidal turbine, enabling the study of the effect of flexible blades on the performance of those devices with high ecological potential. The study focuses on a single tip-speed ratio (equal to 2), the key non-dimensional parameter describing the operating point, and solidity (equal to 1.5), quantifying the robustness of the turbine shape. Both parameters are standard values for cross-flow tidal turbines. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This led to a final temporal resolution of 1 kHz. Further details of the method are provided in Hoerner et al 2021. The resulting flow fields of size i, j were presented dimensionless by the velocities relative to the mean flow speed v of the entire measurement take.…”
Section: Particle Image Velocimetrymentioning
confidence: 99%
“…This led to a final temporal resolution of 1 kHz. Further details of the method are provided in Hoerner et al 2021. The resulting flow fields of size i, j were presented dimensionless by the velocities relative to the mean flow speed v of the entire measurement take.…”
Section: Particle Image Velocimetrymentioning
confidence: 99%
“…Oceanic currents are an unexploited source of green energy with great potential and could seriously strengthen energy security. Hoerner et al [28] experimented with hydrokinetic vertical-axis or cross-flow tidal turbine (CFTT) morphing blades. They concluded that the flexibility of the camber-morphing airfoil has a significant impact on the wake structure and allows less accidental wake changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…The search for truly sustainable sources of energy has translated into renewed interest in low-power, low-impact small-scale hydraulic power devices. Those devices notably include devices that bypass traditional dam-based installations, whose biological and hydropower performance were investigated in recent research [1,2], as well as hydrokinetic turbines (e.g., [3,4]), which may be installed on floating or unchanneled installations. One type of hydrokinetic device that is of particular interest in this work is the free-stream water wheel.…”
Section: Introductionmentioning
confidence: 99%